THE EFFECTS OF FAMILY CONFLICT ON THE PSYCHOLOGICAL NEEDS AND EXTERNALISING BEHAVIOUR OF PREADOLESCENTS - Kader, Zainab; Roman, Nicolette (Social Work/Maatskaplike Werk, 2018)
Families play an important role in the development of individuals. The experiences that occur in the family can either promote or hinder the development of its members. This study aimed to determine the effects of family conflict on preadolescents’ basic psychological needs and externalising behaviour using the Family Environment Scale (FES), Basic Psychological Needs Scale (BPNS), Youth Self-Report (YSR) and Buss Perry Aggression Questionnaire (BPAQ). A quantitative cross-sectional correlational design was employed. The sample consisted of 128 preadolescents (MeanAge = 11.15). The findings indicated a significant positive relationship between family conflict, psychological needs and the externalising behaviour of preadolescents.